2013
DOI: 10.1371/journal.pone.0065200
|View full text |Cite
|
Sign up to set email alerts
|

Homology Modeling of Human γ-Butyric Acid Transporters and the Binding of Pro-Drugs 5-Aminolevulinic Acid and Methyl Aminolevulinic Acid Used in Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) is a safe and effective method currently used in the treatment of skin cancer. In ALA-based PDT, 5-aminolevulinic acid (ALA), or ALA esters, are used as pro-drugs to induce the formation of the potent photosensitizer protoporphyrin IX (PpIX). Activation of PpIX by light causes the formation of reactive oxygen species (ROS) and toxic responses. Studies have indicated that ALA and its methyl ester (MAL) are taken up into the cells via γ-butyric acid (GABA) transporters (GATs). Uptake v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…4345 Consistent with this picture, we find that 5-ALA uptake and PpIX production in CHO-K1 cells is attenuated by the presence of GABA. 43 However, added GABA does not diminish the enhanced PpIX production caused by additive 2 , suggesting that 2 promotes cell uptake of 5-ALA by a process that does not involve the endogenous amino acid transport system.…”
Section: Discussionsupporting
confidence: 81%
“…4345 Consistent with this picture, we find that 5-ALA uptake and PpIX production in CHO-K1 cells is attenuated by the presence of GABA. 43 However, added GABA does not diminish the enhanced PpIX production caused by additive 2 , suggesting that 2 promotes cell uptake of 5-ALA by a process that does not involve the endogenous amino acid transport system.…”
Section: Discussionsupporting
confidence: 81%
“…[28][29][30][31] Derivatives of ALA with improved lipophilicity potentially increase the passive uptake of the PS pro-drug by diffusion and therefore render cellular incorporation independent of (energy-requiring) transporters such as the PEPT1/2 or GABA transporters, which have been suggested as a shuttle for the zwitterionic ALA. [16][17][18][19][20][21] As the uptake process is generally considered as the rate-limiting step in PPIX generation from exogenous ALA (and derivatives), higher levels of the PS and, additionally, increased tissue penetration may be achieved if lipophilic ALA derivatives are applied instead of the original substance. It is based on the tumor cell's ability to generate high intracellular amounts of the PS PPIX upon addition of exogenous ALA. Several mechanisms have been suggested as basis for the high tumor selectivity of ALA-PDT observed during clinical application, among which increased transport in proliferating cells and the altered heme metabolism of cancer cells are reported as explanations.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect may explain low tissue penetration depth, nonhomogenous distribution of PPIX following topical application as well as the limited response of noduloulcerative basal cell carcinoma to ALA-PDT. [16][17][18][19][20][21] In contrast, uptake of the more lipophilic HAL is considered to take place mainly by diffusion and endocytosis. Along with much better tissue penetration, lipophilic derivatives instead of the original ALA yield higher amounts of intracellular PPIX, which, in turn allows for shorter incubation periods and/or lower concentrations of the prodrug.…”
Section: Introductionmentioning
confidence: 99%
“…Baglo et al . concluded that 5‐ALA might be a substrate of GAT2 by constructing homology models of GATs. Further, the reduced expression of GAT2 in the DLD‐1 and HeLa cells led to a decrease in the accumulation of PpIX, suggesting that 5‐ALA could be transported through GAT2 .…”
Section: Discussionmentioning
confidence: 99%
“…Chemically, 5-ALA has a similar structure to GABA with amino and carboxyl groups on both ends, but 5-ALA has one more carbonyl group (C=O) (22). Baglo et al (23) concluded that 5-ALA might be a substrate of GAT2 by constructing homology models of GATs. Further, the reduced expression of GAT2 in the DLD-1 and HeLa cells led to a decrease in the accumulation of PpIX, suggesting that 5-ALA could be transported through GAT2 (24).…”
Section: Discussionmentioning
confidence: 99%